Child Protection, Identity Construction and Media. The Regulation of Audiovisual Content for Minors in Spain - Nogales-Bocio, Antonia I. (2020)
Childhood is a key stage in the assimilation of values and behavioural patterns that shape identity. Among the socializing agents that influence this complex process are the audiovisual media. Therefore, the products that are made available to children and the protection of the child from harmful contents are essential to complete the training process in such a sensitive period of cognitive development. In this research we analyze the influence of television content in the process of constructing the identity of the child as well as the regulatory framework of audiovisual protection applied in Spain. A decade after the entry into force of Law 7/2010 of 31 March, General of Audiovisual Communication (LGCA), many of the challenges posed remain unresolved. As main conclusions we stress the need to respect the special protection schedule, the incorporation of thematic descriptors in the signalling of audiovisual products and a complete legislative categorization of harmful contents to children’s and young people’s development.